A Finite Element Model of Transient Galvanic Corrosion Behaviour of Aluminium Alloy - Jieshun Tang; Mingyang Gao; Haitao Wang; Daokui Xu; Shu Guo; En‐Hou Han (Electrochemical Science Advances)
ABSTRACT The environment in which aircraft are used is very complex, and factors such as high salinity, high humidity atmospheric conditions and mechanical loads applied to the aircraft during flight can lead to damage to the fuselage materials and compromise the safety of the aircraft. A large number of mechanical structural components in aircraft consist of aluminium alloys, which are susceptible to mechanical loads that erode mechanical properties and endanger the integrity of the aircraft. A time‐dependent numerical model is developed in this study. The model provides insight into the complex effects of mechanical loading on the kinetics of galvanic coupling corrosion of AA7075 (aluminium alloy). Our results clearly show that mechanical loading accelerates galvanic corrosion, and the galvanic corrosion behaviour of aluminium alloys is significantly accelerated when loading induces plastic deformation; changes in the thickness of the thin liquid film affect the galvanic corrosion of the galvanic coupling model, which is suppressed when the film thickness is increased, and, in general, exhibits a stronger tendency to corrode homogeneously; the galvanic corrosion behaviour of aluminium alloys is significantly accelerated as the area of cathode increases; the simulation also reveals a higher localisation rate of the model when the boundary load is applied compared to the no‐load case in the galvanic coupling corrosion behaviour. The numerical methodology illustrated in this study not only serves as a comprehensive tool for interpreting the intricate relationship between mechanical loading and corrosion behaviour, but also provides a framework for a deeper understanding of this multifaceted phenomenon. In practical applications, the model developed in this study can be used to check the safety of aluminium alloy structural components in service, which can be used as a reference for the design of aircraft wing skins.